Real-world automotive particulate matter and PAH emission factors and profile concentrations: Results from an urban tunnel experiment in Naples, Italy. (September 2016) - Riccio, A.; Chianese, E.; Monaco, D.; Costagliola, M.A.; Perretta, G.; Prati, M.V.; Agrillo, G.; Esposito, A.; Gasbarra, D.; Shindler, L.; Brusasca, G.; Nanni, A.; et al.
Abstract: On-road particulate matter (PM) mass was measured during a sampling campaign in March of 2015 in the '4 giornate' tunnel in Naples, Italy. Two sets of samples were collected at both sides of the tunnel, each set representing the daily cycle at a 1 h time resolution. Distance-based – mass per kilometer – and fuel-based – mass per burned fuel – emission factors (EFs) were calculated using mass concentrations, traffic flow rates and wind speed as a function of fleet composition. Also, chemical analyses were performed for polycyclic aromatic hydrocarbons (PAHs). Due to the high traffic volume, particle mass concentration at the tunnel exit was always significantly elevated relative to entrance concentration; depending on the hour of the day, PM10 concentration ranged between 300 μ g/m 3, during the early afternoon, and 600 μ g/m 3 during rush hours at the tunnel exit. Correspondingly, PAHs achieved concentrations as high as 1450 ng/m 3, and benzo(a)pyrene, a surely carcinogenic compound, achieved concentrations as high as 69 ng/m 3, raising serious concerns in relation to population exposure close to this urban tunnel. Distance-based and fuel-based emission factors for CO2, PM10 and PAHs were estimated, but while the EF for CO2 was within the range of expected values, the present study found much higher EFs for particulate matter and PAHs. According to the national official statistics from ISPRA (the Italian Institute for the Protection and Research on Environment), derived from the COPERT database, we expected an EF for particulate matter of about 55 mg/km, but the EF estimated from measurements taken at both sides of the tunnel was about four times higher than that expected; also, benzo(a)pyrene achieved an average EF of 2.7 μ g/km, about three times higher than that expected from the ISPRA database. Highlights: Real-world road traffic emissions from the Naples urban area have been determined for the first time A statistically sound approach has been used to determine PM and PAH profile emissions from experimental data The reliability of official statistics has been assessed in the light of experimental data